Analisis Koreksi Fiskal Terhadap Pajak Penghasilan Badan Pada Perusahaan Pt Asco Kontainer Di Tahun 2023-2024 - Prasetyo, Loventina Josephine (Peneliti.net, 2026)
This study examines the impact of fiscal correction on the calculation of Corporate Income Tax, with a focus on aligning commercial financial statements with the provisions of the Indonesian Income Tax Law. The main objective of this research is to understand and identify the effects of fiscal correction on the corporate income tax of PT Asco Kontainer Terminal during the 2023–2024 period, and to determine whether the company's financial statements comply with prevailing tax regulations. Fiscal correction are made to reconcile commercial accounting with Indonesia’s tax regulations. This research adopts a qualitative approach using descriptive analysis to deeply explore the phenomenon under study. The subject of the research is PT Asco Kontainer Terminal, and the object is the impact of fiscal adjustments on the company. The research findings indicate that the calculation of corporate income tax at the company complies with tax regulations. There are both positive and negative fiscal correction recorded in the financial statements, with the study highlighting that positive fiscal correction had a more significant impact by increasing the tax payable.